A Comparative Linguistic Study on the System of Presentation and Delay between Arabic and Indonesian Languages - Hariyanto; Muhaimin, Abd; Robati, Kisti (STUDI ARAB, 2024)
This study aims to uncover similarities and differences between these languages, particularly from a grammatical perspective. To obtain necessary data, the researcher employed a descriptive-analytical method utilizing relevant literature and research. The comparative analysis method was used to contrast the systems of anteriority and posteriority between the two languages, deriving similarities and differences. Based on the findings, this study identified eight points of similarity in the anteriority and posteriority system between Arabic and Indonesian grammar: placing the modifier before the modified, placing the verb before its object originally, placing the first object before the second object, permitting the anteriority of time and place adverbs and their posteriority, similar to their referents, placing the number before the counted object, delaying moral emphasis (all, every) on the affirmed, permitting the posteriority of the object and the anteriority of the subject. Regarding points of divergence, particularly in the anteriority and posteriority system between Arabic and Indonesian grammar, nine aspects were identified: Arabic has rules allowing, necessitating, or prohibiting the anteriority of the modifier to its referent, the anteriority of the object to the verb and subject, and the anteriority of the counted object to the number sometimes. Additionally, Arabic differs from Indonesian in anteriority of demonstrative pronouns to their referents, anteriority of the subject to the verb in the Indonesian structure, anteriority and posteriority of interrogative pronouns in Indonesian, anteriority of the adjective to its noun in Indonesian, and the anteriority of the absolute object in Indonesian, contrasting with Arabic norms.